2004
DOI: 10.1016/j.polymer.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of graft copolymers of methyl methacrylate and poly(n-hexyl isocyanate) macromonomers

Abstract: Living poly(n-hexyl isocyanate) (PHIC) was deactivated with methacryloyl chloride to produce methacryl-terminated poly(n-hexyl isocyanate) (PHIC-MA) rodlike macromonomers. Radical copolymerization of methyl methacrylate (MMA) with PHIC-MA was performed using 2, 2'-azobis(isobutyronitrile) as an initiator in benzene at 60°C to prepare poly(methyl-2-methacrylate)-graft-poly(n-hexyl isocyanate) (PMMA-graft-PHIC) graft copolymers. The monomer reactivity ratios of MMA (M 1) and PHIC-MA (M 2) were evaluated as r 1 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…However the weight loss of the grafted collagen-Al 2 O 3 /SnO 2 composites was very fast, which only occurred in the range of 210-420 ℃ with a dramatic decrease from 360 to 400 ℃. Furthermore the weight variations of the grafted collagen-S 24 and S 30 were much larger than that of the grafted collagen-xerogel. The original degradation temperature of collagen was only 39 ℃.…”
Section: Thermal Analysismentioning
confidence: 90%
See 3 more Smart Citations
“…However the weight loss of the grafted collagen-Al 2 O 3 /SnO 2 composites was very fast, which only occurred in the range of 210-420 ℃ with a dramatic decrease from 360 to 400 ℃. Furthermore the weight variations of the grafted collagen-S 24 and S 30 were much larger than that of the grafted collagen-xerogel. The original degradation temperature of collagen was only 39 ℃.…”
Section: Thermal Analysismentioning
confidence: 90%
“…The infrared emissvity testing data were given in Table 1, where it was observed that the infrared emissivity 24 : 0.708). As known, there were two main modes of heat transfer (infrared energy) through a fibrous insulator: (1) the heat conduction through the gas filling the space between the fibers, and (2) the heat transferred by thermal radiation that was emitted, absorbed, and scattered by the fibers.…”
Section: Infrared Emissivity Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The M GPC n star values correspond to the dimensions of the star polymers in THF as a result of the mechanism of the GPC measurements. Hence, the M GPC n star = M LALLS n star ratios might correspond to the specific volume ðv star s Þ of the poly(PSM) n star polymers in THF [29]: …”
Section: The Specific Dimensions Of the Poly(psm) N Star Polymersmentioning
confidence: 99%